Aspectes sintàctics de l'occità antic comparats amb els del català - Moran i Ocerinjauregui, Josep (Caplletra. Revista Internacional de Filologia, 2006)
The existence of a two cases declension system in medieval Occitan, which lacked in Catalan, was one of the most remarkable differences between both languages. Thisdistinction arises when comparing the homilies from Tortosa, in Occitan, to the ones from Organyà, which are the Catalan translation from Occitan texts.